2004
DOI: 10.1177/095632020401500104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of ATP-Binding Site Directed Potential Inhibitors of Nucleoside Triphosphatases/ Helicases and Polymerases of Hepatitis C and other Selected Flaviviridae Viruses

Abstract: Hepatitis C virus (HCV), West Nile virus (WNV), Japanese encephalitis virus ( JEV), and dengue virus (DENV) are members of Flaviviridae. They are deadly human pathogens and new and better therapeutic strategies are desperately needed. However, there are considerable barriers to the development of anti-Flaviviridae therapeutics, including the persistence of the virus, its genetic diversity during replication in the host and, for example, in the case of HCV, the lack of reproducible infectious culture systems. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…59 Inhibitors of nucleoside triphosphatase (NTPase)/helicase activities of Flaviviridae have not shown promising results against WNV in vitro. 60 IFN-2b inhibits growth of WNV in vitro and can protect BALB/c mice and golden hamsters from WNV-induced disease, although its efficacy is greatly diminished when treatments are delayed beyond 4-6 hours before viral challenge. 41,44,58 IFN-/ -receptor knockout mice have increased mortality following WNV challenge, whereas treatment of primary mouse neuronal cultures with IFN-before or after infection increased neuronal survival in dependently of the effect on WNV replication.…”
Section: Current Treatment and Prospects For Future Therapies Therapementioning
confidence: 99%
“…59 Inhibitors of nucleoside triphosphatase (NTPase)/helicase activities of Flaviviridae have not shown promising results against WNV in vitro. 60 IFN-2b inhibits growth of WNV in vitro and can protect BALB/c mice and golden hamsters from WNV-induced disease, although its efficacy is greatly diminished when treatments are delayed beyond 4-6 hours before viral challenge. 41,44,58 IFN-/ -receptor knockout mice have increased mortality following WNV challenge, whereas treatment of primary mouse neuronal cultures with IFN-before or after infection increased neuronal survival in dependently of the effect on WNV replication.…”
Section: Current Treatment and Prospects For Future Therapies Therapementioning
confidence: 99%
“…212 HCV helicase activity is inhibited in vitro by recombinant antibodies, 213,214 by RNA aptamers 215,216 and by peptides. 217,218 Targeting the nucleotide binding site of HCV-NS3 has proven exceedingly difficult, 219 although nucleotide-mimicking competitive inhibitors have been identified. 220,221 Ring-expanded nucleoside and nucleotide analogs have been shown to selectively inhibit HCV, West Nile Virus, and Japanese encephalitis virus NS3 helicases in vitro without affecting the activity of a control host helicase.…”
Section: Rna Helicases As Drug Targetsmentioning
confidence: 99%
“…The ATP-binding site has been successfully targeted by kinase and gyrase inhibitors in which the binding site is a distinct and well-defined 'pocket' . By contrast, only weak inhibitors have been found that inhibit the HCV binding site 86 . One explanation might be that the HCV helicase NTP-binding site at the interface of domains 1 and 2 has little specificity -it binds all NTPs primarily through the phosphate, not the base, of the nucleotide.…”
Section: Efforts To Develop Hcv Inhibitorsmentioning
confidence: 99%